C-C Motif Chemokine 5 Attenuates Angiotensin II–Dependent Kidney Injury by Limiting Renal Macrophage Infiltration - Rudemiller, Nathan P. (Am J Pathol, 2016)
Inappropriate activation of the renin angiotensin system (RAS) is a key contributor to the pathogenesis of essential hypertension. During RAS activation, infiltration of immune cells into the kidney exacerbates hypertension and renal injury. However, the mechanisms underpinning the accumulation of mononuclear cells in the kidney after RAS stimulation remain unclear. C-C motif chemokine 5 (CCL5) drives recruitment of macrophages and T lymphocytes into injured tissues, and we have found that RAS activation induces CCL5 expression in the kidney during the pathogenesis of hypertension and renal fibrosis. We therefore evaluated the contribution of CCL5 to renal damage and fibrosis in hypertensive and normotensive models of RAS stimulation. Surprisingly, during angiotensin II-induced hypertension, CCL5-deficient (knockout, KO) mice exhibited markedly augmented kidney damage, macrophage infiltration, and expression of proinflammatory macrophage cytokines compared with wild-type controls. When subjected to the normotensive unilateral ureteral obstruction model of endogenous RAS activation, CCL5 KO mice similarly developed more severe renal fibrosis and greater accumulation of macrophages in the kidney, congruent with enhanced renal expression of the macrophage chemokine CCL2. In turn, pharmacologic inhibition of CCL2 abrogated the differences between CCL5 KO and wild-type mice in kidney fibrosis and macrophage infiltration after unilateral ureteral obstruction. These data indicate that CCL5 paradoxically limits macrophage accumulation in the injured kidney during RAS activation by constraining the proinflammatory actions of CCL2.